Bimodal AIDS Vaccine Approach: Induction of cellular as well as humoral immunity can protect from systemic infection - Rasmussen, Robert A. (Vaccine, 2010)
HIV clade C (HIV-C) strains comprise ~56% of all HIV infections worldwide, and AIDS vaccines intended for global use must protect against this subtype. Our vaccine strategy has been to induce balanced antiviral immunity consisting of both neutralizing antibody and cell-mediated immune responses, an approach we tested in primates. As reported earlier, after isolating recently transmitted HIV-C strains from Zambian infants, we used env from one such virus, HIV1084i, to generate a multimeric gp160 immunogen. From another virus, isolated from a different child of the same mother-infant cohort, we cloned env to generate a recombinant simian-human immunodeficiency virus (SHIV), which was adapted to rhesus monkeys to yield SHIV-1157ip. Infant macaques were immunized with recombinant viral proteins, including multimeric HIV-C Env 1084i. To test whether cross-protection could be achieved, we mismatched HIV-C Env immunogens and challenge virus env. All vaccinated and control monkeys were exposed orally to low-dose SHIV-1157ip. Animals with no or only transient infection were rechallenged intrarectally with a high dose of R5 SHIV-1157ipd3N4, a "late”, animal-evolved variant of SHIV-1157ip. Compared to controls, the vaccinees had significantly lower peak viral RNA loads, and one vaccinee remained completely virus-free, even in lymphoid tissues. Data from our novel heterologous mucosal challenge model and our protein-only immunogens imply that significant protection against heterologous viruses circulating in the local community may be achievable with a strategy that seeks to simultaneously induce cellular immunity as well as neutralizing antibody responses.